Innovation and corporate governance in the firm - an empirical analysis with a focus on patents and ownership structure - Grünebaum, Tim (Technische Universität Dortmund, 2021)
This thesis aims at better understanding the complete process of knowledge production in the firm with a focus on Corporate Governance. I theoretically and empirically investigate firm decisions on innovation throughout a concept called the Innovation Value Chain (IVC). This concept includes all relevant firm decisions regarding developing innovative strategies. It starts at evaluating when firms innovate and – if they do – how much they invest in Research and Development (R&D) activities. Next it investigates which factors affect the transition from innovation input into actual tangible innovative assets. In case innovation projects are successful, I evaluate their actual value for the firm. Chapter 2 of this thesis offers a summary of the concept of innovation in the firm, a literature review on how it is affected by Corporate Governance, a discussion on innovation and patent measures as well as descriptive evidence on patenting activities of German firms. Chapter 3 investigates both the investment decision of firms as well as how these investments are transformed into innovative assets. These assets are – unlike in most other concepts – divided into different consecutive measures: Patent applications, patent grants and patent citations. In doing so we are able to address a project’s quality and novelty. A particular focus lies on the role of Corporate Governance in the form of ownership structure. It turns out that – whereas R&D investments are not affected by such structures – firms where managers own shares (owner-led firms) underperform in transferring investments into patents. Moreover – if they innovate – they rather focus on less risky worldwide conformity in innovation. On the other hand it turns out that firms benefit from monitor ownership, thus owners in the supervisory board that tend to control managers. Other control channels like capital concentration and institutional ownership also do not prove beneficial for firm-level innovation. Chapter 4 examines the effect of successful innovation on different performance measures. It turns out that patent grants and citations both increase sales in a production function environment, whereas there was no impact on return on assets and return on equity. Concerning ownership information the results again speak in favor of monitor rather than managerial ownership. Firms should thus endow monitors with shares to increase their effort and interest in the firm. Also owners should withdraw from management positions and rather carry out controlling duties. Chapter 5 focuses on the effect of innovation on firm survival. I am able to confirm the results from former studies that innovation decreases the probability of market exit. Furthermore the opinion of a stable effect throughout a firm’s life cycle is rejected. Whereas mature firms benefit from innovation by strategic renewal when competitors have caught up, young firms should rather stick to conventional investments rather than risky innovation. In summary this thesis helps in better understanding the complete process of knowledge production within the firm. It addresses ownership structure as a crucial factor of Corporate Governance which can be chosen by the firm as well as the role of different patent measures and their impact on different performance dimensions. Firms are thus encouraged to pick adequate Corporate Governance techniques in combination with clear innovation and performance goals, as links can be complex.
Keywords: Innovation; Patents; Ownership structure; Panel data; Firm performance; Firm survival; Corporate governace; 330; Unternehmen; Eigentümer; Innovation; Patent; Panelanalyse